Human rights, social networks and judicial protection:: Criteria to resolve conflicts between rights in light of the international obligations of the State - Nash Rojas, Claudio (Revista Chilena de Derecho y Tecnología, 2024)
This article analyzes the conflicts between human rights that arise in the context of the use of social networks. The current constitutional and legal regulations are reviewed; the jurisprudence is analyzed on two relevant topics, such as the right to be forgotten and funas or scratch; and, finally, some criteria are proposed for the resolution of cases in the national justice system so that it adapts to international standards on freedom of expression. The study seeks to demonstrate the deficits in legislation and judicial interpretation that are preventing the full enjoyment and exercise of freedom of expression through social networks in Chile and proposes some criteria that would allow this situation to be overcome.